Pentingnya Hak Pemilihan Umum dalam Proses Demokratisasi - Devina Cahya Kamila; Anggita Dita Sari; Andika Putra Kamajaya; Gamaliel Yudo Widiyanto; Arvi Octaviana; Unggul Pamekas; Kuswan Hadji (Lembaga Pengembangan Kinerja Dosen, 2024)
Elections or general elections have an important role in determining the future of the nation by electing leaders and officials who are directly elected by the people and for the people. Democracy is the main factor in holding elections as people are free to choose according to their conscience without any coercion or threat. However, the process of implementing elections in Indonesia still experiences obstacles such as the white group (golput) who choose to give up their voting rights in determining the future of the nation. Therefore, we provide solutions and suggestions that can be used to reduce the percentage of the white group by means of election education, voting training, encouraging political parties to be more active, using the media to publish information about elections, election monitoring, research and opinion surveys as described in this research article that we wrote in the hope that it will create a movement to suppress white groups who throw away their voting rights. Then, in compiling this research article, we used an empirical juridical qualitative research method by raising two problem formulations that are problems in the current era. With the results of this research article, hopefully it can help you and can be a source of reference in preparing research that has the same aims and objectives.